Negotiating and navigating global health : case studies in global health diplomacy - Rosskam, Ellen, 1960-; Kickbusch, Ilona, 1950- (Singapore ; Hackensack, NJ : World Scientific, 2012)
Provides insight on how negotiations on global health issues have transpired, the successes, challenges, failures, tools and frameworks for negotiation, mechanisms of policy coherence, ways to achieve global health objectives internationally, and how global health diplomacy used as a foreign policy tool can improve relations between nations.
Introduction: The Art and Practice of Conducting Global Health Negotiations in the 21st Century; Navigating the Negotiating Space Between Geneva and New York: A Case Study in Foreign Policy and Global Health; Public Health Diplomacy in the WTO: Experience from Developing Countries in Negotiations on Health and Related Services in GATS and Issues Related to Public Health in TRIPS; Negotiating the Framework Convention on Tobacco Control: Public Health Joins the Arcane World of Multilateral Diplomacy; Negotiating the International Health Regulations (IHR); Transformative Diplomacy: Negotiation of the WHO Global Code of Practice on the International Recruitment of Health Personnel; Negotiating Issues Related to Pandemic Influenza Preparedness: The Sharing of Influenza Viruses and Access to Vaccines and Other Benefits; Negotiating Equitable Access to Influenza Vaccines: Global Health Diplomacy and the Controversies Surrounding Avian Influenza H5N1 and Pandemic Influenza H1N1; Preparing for Health Diplomacy Negotiations - Global Governance and the Case of Taiwan, WHO, and SARS; China's Engagement with Global Health Diplomacy: Was SARS a Watershed?; Destruction of the Smallpox Virus Stocks: Negotiating for Consensus in the World Health Organization; Negotiating in the World Health Organization: The Intergovernmental Working Group on Intellectual Property, Innovation, and Public Health; Taking the Fight Beyond Official Negotiations: Stakeholders Mobilise Against Counterfeit Drugs; Global Health Workforce Alliance: Negotiating for Access to Health Workers for All; The US President's Emergency Plan for AIDS Relief: Negotiating a Recreation in Global Health and Development; Negotiating ARV Prices with Pharmaceutical Companies and the South African Government: A Civil Society/Legal Approach; Negotiating Health Reform in Kyrgyzstan: Government Management of Donors and Stakeholders; Yellow Fever and Health Diplomacy: International Efforts to Stop the Urban Yellow Fever Outbreak in Paraguay; Diplomacy and the Polio Immunization Boycott in Northern Nigeria.
Includes bibliographical references and index.
Keywords: Public health -- International cooperation; World Health; International Cooperation